Pharmacognostic study of complex phytotherapeutic composition "Detox composition" - A. G. Barsegyan; A. A. Markaryan; M. S. Bardakhanova (Acta Biomedica Scientifica, 2014)
We realized pharmacognostic study of 6-component composition recommended as a therapeutic and prophylactic agent at the hepatic and bile passages disorders, for the accelerated elimination of products of kidneys' nitrogen metabolism and for normalization of lipid metabolism. The norms of indices defining composition's quality and also significant macro- and microscopic characteristics are determined. As the result of phytochemical research we identified main groups of biologically active substances.